Opportunities and Challenges for Indonesian Rattan Furniture Exports to the Japanese Market in 2025 - Opi Yanti (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the opportunities and challenges affecting Indonesian rattan furniture exports to the Japanese market in 2025. The research adopts a non empirical qualitative approach using descriptive analytical methods based on a systematic review of secondary data obtained from government publications, trade reports, industry statistics, policy documents, and relevant academic literature. SWOT analysis is employed as the primary analytical framework to evaluate internal and external factors influencing export competitiveness. The findings reveal that increasing demand for environmentally responsible products, preferential market access through the Indonesia Japan Economic Partnership Agreement, and Indonesia’s positive market position in Japan provide significant opportunities for export expansion. The analysis also identifies important internal strengths, including resource availability, manufacturing capability, design flexibility, and export experience. Nevertheless, export growth remains constrained by intense international competition, strict regulatory requirements, supply chain vulnerabilities, logistics related challenges, and sustainability pressures. The study concludes that strengthening innovation, product quality, regulatory compliance, and sustainable production practices is essential for improving competitiveness. Strategic collaboration among government institutions, industry actors, and supporting stakeholders is required to support long term export development and market expansion in Japan.